1998
DOI: 10.1300/j144v01n02_03
|View full text |Cite
|
Sign up to set email alerts
|

Soil and Plant Testing Programs as a Tool for Optimizing Fertilizer Strategies

Abstract: Soil and plant testing programs are still based o n 'trial and error' methods and lack scientific underpinning in terms of relevant soil chemical and plant nutritional processes, and are site-specific. The programs are valuable when the objective is to diagnose and predict deficiencies of plant nutrients. The programs are less valuable for refined fertilizer strategies, like Integrated Nutrient Management, which are essential in the near future to satisfy changing agricultural, environmental, economic and legi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…Climate and cultivar effects could also be factored in. Van Erp and Van Beusichem (1998) suggested that a more scientific approach and a more complex system of tissue testing would be desirable if it is to be used to its full advantage. Hochmuth (1995) recognized the need to standardize sampling procedures because labs often have difficulty providing diagnoses and recommendations due to incorrect sample collection.…”
Section: Discussionmentioning
confidence: 99%
“…Climate and cultivar effects could also be factored in. Van Erp and Van Beusichem (1998) suggested that a more scientific approach and a more complex system of tissue testing would be desirable if it is to be used to its full advantage. Hochmuth (1995) recognized the need to standardize sampling procedures because labs often have difficulty providing diagnoses and recommendations due to incorrect sample collection.…”
Section: Discussionmentioning
confidence: 99%
“…The increased mean Cu content in Canadian organic arable soils (17,20) was explained by parent material differences and Cu applications to these soils. The increased mean Cu content in Canadian organic arable soils (17,20) was explained by parent material differences and Cu applications to these soils.…”
Section: Resultsmentioning
confidence: 95%